A new species of Phyllotreta Chevrolat, 1836 (Coleoptera: Chrysomelidae: Galerucinae: Alticini) from Omsk Province of Russia with comments on Phyllotreta species diversity in Northeastern Palearctic - Konstantinov, A. S.; Moseyko, A. G. (Zootaxa, 2019)
A new species of flea beetle genus Phyllotreta Chevrolat, 1836 (P. sholaksori new species) is described from shores of saline lakes in Southwestern Siberia. It is compared with species with which it was collected as well as with species comprising a group to which it belongs (P. araxicola Jablokoff-Khnzorian, 1968, P. astrachanica Lopatin, 1977, P. atra Fabricius, 1775, P. balcanica Heikertinger, 1909, P. cruciferae Goeze, 1777, and P. diademata Fourdas, 1860). All these species are illustrated and included in the key.